Laser lock-in thermography for residual stress characterization on metallic plate - Chong, Jun Jian (2019)
Everything we see around us is made of materials. There is a diverse range of materials in the world and each has its own unique properties and uses. They can be a simple material by itself or a composite of various materials with significant different physical and chemical properties, when combined, produces a new material with different characteristics. In the engineering industry, manufacturing machines are essential to production. Majority of the machines and their parts are made of metal or composite metal. A common issue faced in the production is machinery breakdown. Machinery breakdown is usually caused by the failure of materials especially in the autonomous production. Materials are subjected to tensile and compressive forces during the production process. Theses stresses remain in the materials even after all the internal and external loadings forced have been removed and they are called residual stresses. Residual stress is the stress which retained within the materials prior to the application of in-service load. Residual stress has various effects on the performance of the material. It can be either beneficious or detrimental in many cases. For example, residual stress can increase or decrease the mean stress applied over a cycle of fatigue. By using Gerber or Goodman relations, quantification of the effect on lifespan is made possible. Mean stress can be increased by a tensile residual stress retained in the material. Hence, for the lifespan to remain the same, the stress amplitude must be decreased accordingly. In present, there are various measurement techniques available for residual stress. Some of the most commonly used techniques are Hole-Drilling and X-Ray Diffraction method. Hole-Drilling method has one of the highest accuracies in measuring residual stress and is applicable to most of the materials. However, Hole-Drilling is considered a semi-destructive technique as a small area of the material must be removed for measurement. There will be an introduction of additional measured stress due to the drilling which must be taken account into. X-Ray Diffraction is a non-destructive technique as no cutting or any damage will be done to the material for measurement. However, it is only applicable to small component testing and a limited range of material. The paper presents a non-destructive method for residual characterization on metallic plate based on the use of Laser Lock-In Thermography. The basic concept is to characterize residual stress by measuring the value of thermal diffusivity. There is strong relationship between thermal diffusivity and plastic deformation. This is due to the increasing density of dislocation in metallic lattice caused by plastic deformations, which is responsible for carrying in the material. The character of this method is remote, non-destructive and applicable to most materials, be it big or small. This method appears to be the better of some of the most commonly used techniques such as Hole-Drilling and X-Ray Diffraction, complementing the pros of both techniques. Laser Lock-in thermography will provide the user with real-time result and there is little to no processing needed. Most importantly, it can measure the residual stress of the material without any damage to it and can be used during normal working condition. This study will provide the engineers with better option for their preventive maintenance.